Spatial maneuvering in education. Educational experiences and local opportunity structures among rural youth in Norway - Bæck, Unn-Doris K. (Nordic Journal of Comparative and International Education (NJCIE), 2019)
Based on an interview study of upper secondary school pupils in a county in Northern Norway and against a backdrop of spatial differences in dropout rates in upper secondary education in Norway, this article explores the significance of space for understanding the experiences of young people in the transition from lower to upper secondary education. The situation of rural youth is particularly highlighted. Through interviews with students, four factors connected to spatiality and more specifically to spatial mobility have been pinpointed. These are connected to (1) local school structures, (2) local labour markets, (3) being new in a place, and (4) localised social capital. At a more theoretical level, the concept of opportunity structure is employed in order to grasp how structures connected to education, labour market, and economy can have a profound effect on the lives of young people, being subjected to a mobility imperative that has become a particularly relevant driving force for rural youth.